Եկեղեցին՝ ժողով եւ ժողովուրդ (ըստ առաքելական հայրերի գրվածքների) - Հովհաննես Սրկ. Բալայան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Апостольскими отцами церковь не воспринимается сама по себе, отдельно, а в соотношении с другим явлением или событием, например, Богом, конкретной местностью или окружающим ее миром. В этом смысле церковь касается как всех христиан в общем, так и отдельно взятых верующих, проживающих в конкретной общине. С другой стороны, сущность церкви исходит от ее связи с Богом. Иными словами, если нет этой двусторонней встречи или какой-либо из этих сторон, то не может быть и церкви. According to the Apostolic Fathers, the Church is not understood by herself,but rather by the relationship with another reality or phenomenon, such as God, aspecifi c location or the world around her. In this regard, the Church refers to all the Christians together in general, as well as to a specifi c community living in one place. On the other hand, the identity of the Church stems from the relationship with God.In other words, if this bilateral meeting or any of the parties is non-existent, there cannot be a Church either. Each of the Apostolic Fathers.
Keywords: Christianity; Armenian church